Terapi Bekam Thibb al-Nabawi pada Era Modern: Kajian Living Hadis - Zainnurrofiq, Muhammad; Zaki, Muhammad Satrio Wibowo; Mukarromah, Faizzatul; Fauziah, Malihatul (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2024)
This study examines the application of cupping therapy in the context of Thibb al-Nabawi, or the medicine of Prophet Muhammad saw. The author uses qualitative methods and field research to analyze the benefits of cupping therapy and its relevance in the modern era. Cupping, or al-hija>mah, is a traditional method that removes stagnant blood or toxins from the body through the skin. The concept of Thibb al-Nabawi provides a strong foundation for modern cupping therapy, emphasizing cleanliness, caution, and the spiritual dimension in healing. Living hadith supports this practice with the belief that there is a cure for every disease decreed by Allah SWT. Prophet Muhammad saw stated that cupping is the best treatment in Islam. Sunnah cupping practices in Indonesia follow Islamic principles with ethical guidelines and manners reflecting Islamic teachings. The acceptance of cupping therapy by modern society indicates its recognition as a preventive measure to enhance overall health. The transformation of cupping therapy through modern technology maintains the relevance of this traditional practice in contemporary healthcare. This study provides insights into the relevance and positive contributions of cupping therapy in healthcare while preserving Islamic values.